2022
DOI: 10.3390/agriculture12101559
|View full text |Cite
|
Sign up to set email alerts
|

Design and Experiment with a Double-Roller Sweet Potato Vine Harvester

Abstract: The yield of sweet potato vines is large, making it a good source of food. However, it is difficult to harvest sweet potato vines due to creeping and intertwining. Therefore, according to the domestic sweet potato planting model, this paper designed a double roll sweet potato vine harvester which can complete the operations of vine picking, vine killing, conveying and header harvesting at one time. The machine adopts the process of front roll vine picking, rear roll vine killing and rod bar lifting. The key co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Regarding the lifting chain, it usually consists of two stages of cleaning. Chain's vibration and impact, with the lifting chain rod, are the main method of the lifting chain to separate the soil from the tuber [56][57][58][59][60]. When combined with the vibrator, the lifting chain will produce a wider vibration amplitude, which can enhance the cleaning effect [61].…”
Section: Structure Optimizationmentioning
confidence: 99%
“…Regarding the lifting chain, it usually consists of two stages of cleaning. Chain's vibration and impact, with the lifting chain rod, are the main method of the lifting chain to separate the soil from the tuber [56][57][58][59][60]. When combined with the vibrator, the lifting chain will produce a wider vibration amplitude, which can enhance the cleaning effect [61].…”
Section: Structure Optimizationmentioning
confidence: 99%
“…On the other hand, Salces et al (2000) reported that leaf of the foliage dry matter ranged from 60 -66%, stem from 12 -15%, and petiole from 20 -28% when cassava plants were defoliated at 4 -5 mo after planting. Sweetpotato vines can reach 1 -7 m in length which are mostly returned to the field after harvesting, causing huge waste (Mu et al 2022).…”
Section: Introductionmentioning
confidence: 99%